Positive Personality Model: Which Traits Relate to Complete Mental Health as Conceived by the Dual Factor Model? - de la Iglesia, Guadalupe (2019)
The aim of this research was to study the association between the Positive Personality Model (PPM) traits and the state of complete mental health as conceived by the Dual Factor Model (DFM). The sample was composed of 1502 Argentinean adults from the general population (age: M = 39.79, SD = 14.23; gender: 50.1% male, 49.9% female). A cluster analysis replicated the four-group classification of the DFM: complete mental health, symptomatic but content, troubled and vulnerable. The complete mental health cluster showed a significantly higher presence of sprightliness, serenity, moderation and integrity than the other groups. As for humanity, the complete mental health and the symptomatic but content groups had the highest scores. Sprightliness and serenity increased the odds of belonging to the complete mental health group while integrity and humanity decreased these odds. Implications for the Argentinean population are discussed.